RSAD2 and AIM2 Modulate Coxsackievirus A16 and Enterovirus A71 Replication in Neuronal Cells in Different Ways That May Be Associated with Their 5′ Nontranslated Regions - Yogarajah, Thinesshwary; Ong, Kien Chai; Perera, David; Wong, Kum Thong (American Society for Microbiology, 2017)
Coxsackievirus A16 (CV-A16) and enterovirus A71 (EV-A71) are closely related enteroviruses that cause the same hand, foot, and mouth disease (HFMD), but neurological complications occur only very rarely in CV-A16 compared to EV-A71 infections. To elucidate host responses that may be able to explain these differences, we performed transcriptomic analysis and real-time quantitative PCR (RTqPCR) in CV-A16-infected neuroblastoma cells (SK-N-SH), and the results showed that the radical S-adenosylmethionine domain containing 2 (RSAD2) was the highest upregulated gene in the antimicrobial pathway. Increased RSAD2 expression was correlated with reduced viral replication, while RSAD2 knockdown cells were correlated with increased replication. EV-A71 replication showed no apparent correlation to RSAD2 expressions. Absent in melanoma 2 (AIM2), which is associated with pyroptotic cell death, was upregulated in EV-A71-infected neurons but not in CV-A16 infection, suggesting that the AIM2 inflammasome played a significant role in suppressing EV-A71 replication. Chimeric viruses derived from CV-A16 and EV-A71 but containing swapped 5' nontranslated regions (5' NTRs) showed that RSAD2 expression/ viral replication and AIM2 expression/viral replication patterns may be linked to the 5' NTRs of parental viruses. Differences in secondary structure of internal ribosomal entry sites within the 5' NTR may be responsible for these findings. Overall, our results suggest that CV-A16 and EV-A71 elicit different host responses to infection, which may help explain the apparent lower incidence of CV-A16-associated neurovirulence in HFMD outbreaks compared to EV-A71 infection.